(3cJGH GdBKGQs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s
(3ChdgG (B:s
(3HGH GdhVhA eMeO Hf GdMSf QMeg Gddg , bGd (B: (3CNHQfG CHh MfjaI QVi Gddg Yfg , Yf MeGO Yf YeQ Hf GdNWGH QVi Gddg Yfg Cfg JhVC aYd jOjg eKfi eKfi s
(3BNQgG (B:s
(3CNHQfG CHh MfjaI QVi Gddg Yfg Yf MeGO Yf EHQGgje , bGd GdHdGA ehcd HGdcde s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI Ydi fSNI bhGe GdOjf GdCQJbGfi hgj fSNI ecJhHI SfI (B494 (3hebGHdI Ydi fSNI GdEeGe GdeUfas
(3HChd GdfSNI bQGAI SfI (B771s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs